Study on the movements and bending stresses of hangers and control measures in self-anchored rail suspension bridges. (15th January 2023) - Wang, Hui; Shen, Ruili; Bai, Lunhua; Wang, Lu; Chen, Wei
Highlights: A frame finite element model (FFEM) for a railway self-anchored suspension bridge is established and validated. An effective method to calculate the bending stresses of hangers based on the FFEM is proposed. New findings of longitudinal movement characteristics and stress of the short hangers in the investigated bridge are presented. Efforts of reducing bending stress of hangers by adding central clamps or adding negative stay cables are investigated. Abstract: As a critical component of suspension bridges, hangers face an increasingly prominent risk of deterioration and even breakage due to relative movement and fatigue stress, posing a serious threat to bridge safety. This study investigated longitudinal movements and bending stresses of short hangers in a typical self-anchored rail suspension bridge using transient dynamic analysis. We proposed an effective method to calculate the bending stresses of hangers based on a frame finite element model (FFEM). The effects of hanger breakage on the dynamic response of bridges were further analyzed. Results showed significant relative longitudinal movements between cables and girders, causing consequential periodic bending stresses on hangers. Furthermore, the bending stresses considerably increased as the lengths of these hangers decreased. The relative longitudinal movements and bending stresses of short hangers exhibited static characteristics in self-anchored suspension bridges. The breakage of hangers induced a significant dynamic response on adjacent hangers, which bore the most redistributed loads and became critical components. Based on the static deformation characteristics of self-anchored suspension bridges, two promising measures—adding central clamps or negative stay cables—were proposed to reduce the bending stresses and improve the fatigue performance of hangers. The improvements of the two measures were comprehensively analyzed and compared. The findings of this study are significant for improving the design of rail self-anchored suspension bridges in terms of hanger safety.